Using energy resources to diversify the economy: Agricultural price distortions in Kazakhstan - Richard Pomfret (Center for Social and Economic Research (CASE), 2007)
The agricultural sector in Kazakhstan experienced declining output throughout the 1990s, partly because relative prices shifted from being distorted in favor of farmers to being distorted against them. After the end of the decade public policy shifted towards support for (or less discrimination against) agriculture, boosted by a billion-dollar Agriculture and Food Program for 2003-5, which was made possible by booming oil revenues. This paper provides estimates of producer support for the main agricultural products in Kazakhstan, and analyses the consequences of shifts in farm support policy. Methodologically, the paper's primary concerns are how to capture the direction and magnitude of price distortions, how to interpret the measures, and what are the policy implications.
Keywords: Q18; Q32; O13; F14; 330; Kazakhstan; diversification; agriculture; Landwirtschaft; Agrarpolitik; Wirtschaftspolitik; Agrarpreis; Diversifikation; Kasachstan